Occupational disease and absenteeism in the workers in one Hospital in Lima -Perú: Enfermedad profesional y ausentismo laboral en los trabajadores de un hospital de Lima- Perú - Suárez Egoávil, Catherine Amparo (2021)
Introduction: Absenteeism from work in public or private institutions is classified as one of the main labor problems. Objective: To determine the association between occupational disease and work absenteeism at the Hospital Policial Augusto Belisario Leguía, in the years 2017-2018. Methodology: A descriptive, cross-sectional, and qualitative-quantitative retrospective study in a convenience sample of 79 medical breaks with a diagnosis of occupational diseases of police health personnel. Collecting data was used. Results: The highest work absenteeism occurred in female patients, married, over 50 years of age, technical nursing profession and with a work seniority of more than 20 years. A global absenteeism rate of 7.56% (2017) and 6.39% (2018) was obtained, a severity index of 25.12 days (2017) and 26.43 days (2018). Conclusions: Occupational diseases caused by physical agents develop greater absenteeism due to musculoskeletal injuries more frequently.